Generalized Hurst Exponent of The Carbon Thin Film Surface - V.N. Borisyuk; Jassim Kassi; A.I. Holovchenko (Журнал нано- та електронної фізики)
Self-similar structure of the carbon thin film surface, obtained by magnetron sputtering, is investigated numerically. Statistical parameters are calculated within two dimensional multi fractal detrended fluctuation analysis. The numerical model of the surfaces under investigation was build from the SEM images of the carbon thin film. It is shown that the self-similarity in surface structure preserves through different resolutions of the SEM images.